Potential causal link between dietary intake and epilepsy: a bidirectional and multivariable Mendelian randomization study - Lai, Shenglong; Xing, Yazhou; Li, Haiyang; Wu, Du; Wang, Lin; Liang, Qinghua (Frontiers in Nutrition, 2024)
Background: Epilepsy is a common neurological disease, and dietary intake has been suggested as a potential modifiable risk factor. However, the causality of associations between dietary intake and epilepsy remains uncertain. This study aimed to investigate the potential causal relationships between various dietary intakes and epilepsy using Mendelian randomization (MR) analysis.A two-sample MR approach was employed, utilizing genetic variants associated with dietary factors as instrumental variables (IVs). Genome-Wide Association Study (GWAS) summary data on dietary intakes were obtained from the UK Biobank, while data on epilepsy were sourced from the European Bioinformatics Institute. The number of genetic variants used as IVs varied for each dietary factor. Inverse-variance weighted (IVW), weighted median, MR-Egger, and Bayesian weighted MR (BWMR) methods were used to assess causality. Multivariable MR (MVMR) was performed, adjusting for potential confounders. Sensitivity analyses were conducted to evaluate the robustness of the findings.The study identified a significant inverse association between non-oily fish intake and epilepsy risk (OR = 0.281, 95% CI: 0.099-0.801, P = 0.018) using the IVW method. This finding was corroborated by the BWMR analysis (OR = 0.277, 95% CI: 0.094-0.814, P = 0.020). The MVMR analysis further confirmed the protective effect of non-oily fish intake on epilepsy risk after adjusting for potential confounders. In the reverse MR analysis, epilepsy was associated with reduced water intake (OR = 0.989, 95% CI: 0.980-0.997, P = 0.011).The present MR study provides evidence of a causal, protective relationship between non-oily fish intake and reduced epilepsy risk. Additionally, the findings suggest that epilepsy may influence water intake patterns. These results contribute to our understanding of the role of dietary factors in epilepsy and may inform dietary recommendations for the management and prevention of this condition.